Sella turcica-Its importance in orthodontics and craniofacial morphology - Haritha Pottipalli Sathyanarayana; Vignesh Kailasam; Arun B Chitharanjan (Wolters Kluwer Medknow Publications, 2013)
The sella turcica is a structure which can be readily seen on lateral cephalometric radiographs and sella point is routinely traced for various cephalometric analyses. The search was carried out using the following key words (sella turcica, bridging of sella, size, shape of sella turcica) and with the following search engine (Pubmed, Cochrane, Google scholar). The morphology is very important for the cephalometric position of the reference point sella, not only for evaluating craniofacial morphology, but also when growth changes and orthodontic treatment results are to be evaluated. This makes it a good source of additional diagnostic information related to pathology of the pituitary gland, or to various syndromes that affect the craniofacial region. Clinicians should be familiar with the normal radiographic anatomy and morphologic variability of this area, in order to recognize and investigate deviations that may reflect pathological situations, even before these become clinically apparent. During embryological development, the sella turcica area is the key point for the migration of the neural crest cells to the frontonasal and maxillary developmental fields. The neural crest cells are involved in the formation and development of sella turcica and teeth. The size of sella turcica ranges from 4 to 12 mm for the vertical and 5 to 16 mm for the anteroposterior dimension. There are many classification systems regarding the shape of sella turcica. Majority of the studies show that about 67% of the subjects had normal appearance and about 33% showed variations. The prevalence of sella turcica bridging is high in class III malocclusions and dental anomalies.